Socioeconomic Status, English Exposure and CLIL Motivation in High and Low Exposure CLIL Groups - Forrest Leah Tompkins (Universitat Autònoma de Barcelona, 2022)
Content and Language Integrated Learning (CLIL) programs are often praised for bringing equity to foreign language learning (e.g., Lorenzo et al., 2020). However, streaming processes, such as those of the Community of Madrid Bilingual Program, may reinforce social inequalities among students (e.g., Llinares & Evnitskaya, 2020). In line with recent research comparing CLIL students' affective factors in high exposure (HE) and low exposure (LE) tracks (e.g., Fernández-Agüero & Hidalgo-McCabe, 2020), the present study examines potential differences in the socioeconomic status (SES), CLIL motivation and exposure to English of HE and LE students at a bilingual (Spanish/English) secondary school in a low SES town in Madrid. A questionnaire measuring cultural and economic capital, CLIL motivation, and teachers' use of English was administered to a sample of LE and all HE students in year 10. Results show that the students of lowest and highest SES were concentrated in LE and HE tracks, respectively. In the LE track, CLIL and English teachers used English less frequently, and students exhibited lower intrinsic motivation. For students with lower English proficiency (often of lower SES), access to the cultural and economic capital afforded by knowledge of English may be constrained by fewer meaningful learning opportunities.